ALICINA E EXTRATO AQUOSO DE BULBO DE ALHO (Allium sativum) NO CONTROLE DA LEPROSE DOS CITROS - Guirado, Nivaldo; Guirado, Cecilia Gatti; Ambrosano, Edmilson José; Arévalo, Roberto Antonio; Rossi, Fabrício; Mendes, Paulo César Doimo (REVISTA DE AGRICULTURA, 2016)
ALICINA E EXTRATO AQUOSO DE BULBO DE ALHO (Allium sativum) NO CONTROLE DA LEPROSE DOS CITROS